Um modelo para apoiar a gestão do conhecimento no gerenciamento ágil de projetos de software - Almeida, Luís Fernando Magnanini de (2016)
The Agile Project Management (GAP) emerges as a response to criticisms made to Traditional Project Management Methods for being prescriptive, bureaucratic, and not very dynamic, thus limited when applied in innovation-intensive and knowledge-intensive environments. The main differences between those approaches are the self-management teams, use of the concept of vision rather than scope, iterations, greater customer involvement and pursuit for simplicity. All have an impact on how Knowledge Management (KM) is performed, in particular, the prioritization of the use of tacit rather than explicit knowledge. Several authors approach the intercession between agile project management and knowledge management theories, however, they made little progress in their proposals for management models. Through systematic theoretical reviews and case studies, we advance in this aspect, proposing a Conceptual Model for Knowledge Management in Agile Project Management. The main peculiarities are: consider both intra and interproject knowledge; consider GAP differentials; focus on the project team; use GAP rituals to potentiate the KM; and the applicability to any agile method.